O princípio da diferença de John Rawls como alternativa ao utilitarismo na economia do bem-estar - Neuberger, Daniele (2015)
This dissertation aims to show that the criticism of John Raws to utilitarianism and the proposition of his Theory of Justice, especially the difference principle, offer an alternative to utilitarianism as a normative basis for the welfare economics, by providing a safe way to arbitrate social and economic inequalities. According to the philosopher, by making the utility as the supreme good, utilitarianism concerns only with maximizing the total happiness, and disregards the way it is distribute among different individuals. When interpersonal utility comparisons were criticized for being considered normative, welfare economy found on the principle of efficiency considered one scientific way to assess the well-being and at the same time, keeping alive the utilitarian tradition. This principle, however, is also criticized by the author, since selects various positions as equally effective, and among which some people can live in abundance while others live in extreme poverty. In this sense, John Rawls proposes a theory of justice in an attempt to offer an alternative to utilitarian perspective. In this theory, individuals are driven to put in a hypothetical situation, called original position, which must decide on the principles that will govern the institutions of their society. The author states that the principles to be chosen in the original position would be, briefly, the principle of equal liberty and the principle of difference. According to the first principle, which has priority over the second, ensures an equal system of basic freedoms for all individuals and, according to the difference principle, social and economic inequalities are allowed only if they occur in favor of individuals less fortunate in society. It is argued that the Rawlsian theory, and especially the principle of difference, is an alternative to utilitarianism as a normative basis of welfare economics. This is because this principle ensures the well-being for all individuals in society, and not only that contribute most to the total satisfaction to increase, as proposed by utilitarianism. In this sense, if taken into account, these contributions would allow the welfare economy fill the gap left by the distributive utilitarianism, and to assess the well-being of individuals in order to guarantee them not only economic efficiency but also distributive justice.